Synthesis of Magnetic Biochar Derived from Oil Palm Frond for Waste Cooking Oil Treatment - Mohamad Ketar@Mokhtar, Nur Izzah; Harun, Hasnida (Progress in Engineering Application and Technology, 2021)
: In today’s world, the oil frying method is widely used, causing the accumulation of waste generated from cooking oil. Improper cooking oil waste management leads to the discharge into the environment causing land and water pollution. In water, oil layer coats the surface and prevents the dissolution of oxygen, leading to a further decreasing availability to living organisms in the water. In order to remove the waste cooking oil from water, this study investigates the potential of magnetic biochar from oil palm fronds as a low-cost bio-adsorbent. The magnetic biochar was characterized by FTIR and SEM. The pyrolysis method was used in the biochar preparation and the co-precipitation method was used to synthesis magnetic biochar. Batch experiments of the magnetic biochar were conducted at different dosages, oil concentration and contact time to find out the optimum condition for the water and oil separation. The magnetic biochar's well-cyclability is also observed. The characterization of magnetic biochar shows strong peak at 2341 cm-1 that represents the symmetric stretch of vibration of strong O=C=O stretching of carbon dioxide and 2113 cm-1 that represents strong N=C=S stretching of isothiocyanate. From the results obtained, the optimum efficiency of magnetic biochar is 120 seconds of contact time in 1% oil concentration by using 1.5g magnetic biochar with separation efficiency of 95%. In addition, after 3 cycles of the adsorption process, the separation efficiency of oil waste was still around 94%. Therefore, this study anticipates that the magnetic biochar from oil palm fronds is a good candidate for application in the clean-up of waste cooking oil that being spill in drainage.